"Click" chemistry mediated construction of cationic curdlan nanocarriers for efficient gene delivery. (1st May 2017) - Han, Jingfen; Wang, Xia; Liu, Lixia; Li, Dongxue; Suyaola, Suyaola; Wang, Tianyue; Baigude, Huricha
Highlights: "Click" chemistry mediated amine functionalization of curdlan. Lysine "clicked" curdlan shows excellent water solubility. Plasmid/Lysine "clicked" curdlan complex forms nanoparticles. Lysine "clicked" curdlan efficiently delivered eGFP plasmid to cancer cells. We report a novel curdlan-based gene delivery system. Abstract: A cationic group has been quantitatively and selectively introduced into C6 position of each glucose units of Curdlan by "Click Chemistry" successfully. The resulting cationic Curdlan-Imidazole-lysine polymers (Cur-6-100Lys) exhibit excellent water solubility. Structure of the Cur-6-100Lys complexes was verified by FTIR and NMR spectroscopic measurements, and analysis of Cur-6-100Lys by GPC, DLS and SEM revealed that they have stoichiometric, nanosized spheroidal structures. Cytotoxicity measurement, electrophoretic mobility shift assay and EGFP-pDNA transfection have been carried out respectively. The results clearly show that Cur-6-100Lys nanocarriers have bound to dsDNA promptly, are less cytotoxic to both 7901 cells and HeLa cells, and are readily able to transport EGFP-pDNA into HepG2 cells. Our studies indicated that Cur-6-100Lys can potentially be used as a versatile nano platform for efficient gene delivery in living cells.